Recurrent childhood animal cruelty and its link to recurrent adult interpersonal violence - Trentham, Caleb E. (International journal of offender therapy and comparative criminology, 2018)
In the early 1960s, researchers began to examine the potential link between childhood animal cruelty and future interpersonal violence. Findings since then have been inconsistent in establishing a relationship between the two. This may be due to researchers failing to measure the recurrency of childhood animal abuse and the recurrency of later violent acts committed in adulthood. The current study, using data from 257 inmates at a medium-security prison in a Southern state, is a replication of research conducted by Tallichet and Hensley, and Hensley, Tallichet, and Dutkiewicz, which examined this recurrency issue. The only statistically significant predictor of recurrent adult interpersonal violence in this study was recurrent childhood animal cruelty. Inmates who engaged in recurrent childhood animal cruelty were more likely to commit recurrent adult interpersonal violence. Respondents’ race, education, and childhood residence were not significant predictors of the outcome variable.